2019
DOI: 10.1063/1.5094787
|View full text |Cite
|
Sign up to set email alerts
|

Deep trap spectra of Sn-doped α-Ga2O3 grown by halide vapor phase epitaxy on sapphire

Abstract: Epitaxial layers of α-Ga2O3 with different Sn doping levels were grown by halide vapor phase epitaxy on sapphire. The films had shallow donor concentrations ranging from 1017 to 4.8 × 1019 cm−3. Deep level transient spectroscopy of the lowest doped samples revealed dominant A traps with level Ec − 0.6 eV and B traps near Ec − 1.1 eV. With increasing shallow donor concentration, the density of the A traps increased, and new traps C (Ec − 0.85 eV) and D (Ec − 0.23 eV) emerged. Photocapacitance spectra showed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 26 publications
3
40
0
3
Order By: Relevance
“…The rectification ratio of forward and reverse current is %10 5 , so when applying reverse bias voltage to the sample, almost all bias voltage is applied to the depletion region of the Schottky contact (see Experimental Section). This result showed that the donor concentration in this SBD was well suppressed compared with that in the study by Polyakov et al, [36] suggesting higher purity and better Schottky characteristic of our sample.…”
Section: C-v Measurementsupporting
confidence: 65%
See 3 more Smart Citations
“…The rectification ratio of forward and reverse current is %10 5 , so when applying reverse bias voltage to the sample, almost all bias voltage is applied to the depletion region of the Schottky contact (see Experimental Section). This result showed that the donor concentration in this SBD was well suppressed compared with that in the study by Polyakov et al, [36] suggesting higher purity and better Schottky characteristic of our sample.…”
Section: C-v Measurementsupporting
confidence: 65%
“…In the studies on α-Ga 2 O 3 previously reported, deep traps located at E c À1 eV, E v þ1.4 eV [35,37] and located at E c À(%2 eV), E c À2.7 eV are confirmed. [36] Here, E v corresponds to the valence band maximum. The PHCAP spectra obtained in the study by Polyakov et al [36] seem to resemble that obtained in this study (Figure 5a).…”
Section: Phcap and Dlosmentioning
confidence: 99%
See 2 more Smart Citations
“…Достигнут значительный прогресс в выращивании эпитаксиальных пленок [1][2][3][4][5][6][7][8][9]. Корундообразная α-фаза обладает среди всех политипов оксида галлия наибольшей шириной запрещенной зоны E g , не менее 5.3 эВ, и при легировании Sn или Si имеет высокую донорную проводимость [3,8,[10][11][12][13][14][15]. В то же время ε-фаза с E g , близкой к 4.9 эВ [1,2,16], является второй после β-Ga 2 O 3 по температурной стабильности.…”
Section: Introductionunclassified